Estabilidad mandibular en el tratamiento integral del paciente adulto (1995)
ABSTRACT: The purpose of this article is to compile some information about concepts of mandibular stability and centric relation. The centric relation is the term or concept that more controversy generates in the field of dentistry, Despite of the historic evolution it constitutes an important aspect in the correction of oclusal problems. The adult patient that request an integral treatment, generally show enormous discrepancy in his or her occlusal scheme. With the treatment the clinician tries to reinforce, recuperate or preserve the physiological occlusion but never creates a new one, so that during, at the end or even after the treatment, mandibular stability is given for a good function of the stomatognatic system.